The Triple Helix of Knowledge: Synergies and Potentialities among Engineering, Art, and Education - Cukierman, Uriel Rubén (International Journal of Engineering Pedagogy (iJEP), 2025)
This analysis explores the “Triple Helix of Knowledge,” examining the synergies between Engineering, Art, and Education, with knowledge as their common denominator. Engineering, rooted in ingenuity, focuses on applying scientific principles to solve problems. Art, stemming from skill and craft, involves mastery for creative expression. Education, encompassing upbringing and development, refines cognitive, practical, and social competencies. All three share a semantic foundation in cultivated skill, novelty generation, and human potential development. The paper proposes this model, building on the Sabato Triangle and the later Triple Helix model of innovation. It argues for a reengineering of engineering education, emphasizing adaptability, critical and creative thinking, and general life skills over encyclopedic knowledge. The integration of art into STEM (STEAM) is highlighted, advocating for a holistic approach that cultivates consciousness and prepares individuals for an AI-driven world. The ultimate goal is to foster professionals who integrate head, heart, and hands, ensuring innovation and relevance in a rapidly changing society.